Optimal Control Problems in Finite-Strain Elasticity by Inner Pressure and Fiber Tension - Günnel, Andreas; Herzog, Roland (Frontiers in Applied Mathematics and Statistics, 2016)
Optimal control problems for finite-strain elasticity are considered. An inner pressure or an inner fiber tension are acting as driving forces. Such internal forces are typical, for instance, for the motion of heliotropic plants, and for muscle tissue. Non-standard objective functions relevant for elasticity problems are introduced. Optimality conditions are derived on a formal basis, and a limited-memory quasi-Newton algorithm for their solution is formulated in function space. Numerical experiments confirm the expected mesh-independent performance.